2016
DOI: 10.1016/j.chembiol.2016.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Fasnall, a Selective FASN Inhibitor, Shows Potent Anti-tumor Activity in the MMTV-Neu Model of HER2 + Breast Cancer

Abstract: Many tumors are dependent on de novo fatty acid synthesis to maintain cell growth. Fatty acid synthase (FASN) catalyzes the final synthetic step of this pathway, and its upregulation is correlated with tumor aggressiveness. The consequences and adaptive responses of acute or chronic inhibition of essential enzymes such as FASN are not fully understood. Herein we identify Fasnall, a thiophenopyrimidine selectively targeting FASN through its co-factor binding sites. Global lipidomics studies with Fasnall showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
118
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(128 citation statements)
references
References 44 publications
9
118
1
Order By: Relevance
“…As a case study, we used the developed platform to study the response to metformin treatment, which preliminarily suggested metformin has differential effects on different lipid classes. In the presence of lipid-rich medium, certain lipids accumulated after metformin treatment, which is consistent with a recent study showing that the certain classes of lipids accumulated in breast cancer cells after treatment with a fatty acid synthase inhibitor (20). Further, as a proof of concept we measured with stable isotopes, the incorporation of glucose into lipids.…”
Section: Discussionsupporting
confidence: 90%
“…As a case study, we used the developed platform to study the response to metformin treatment, which preliminarily suggested metformin has differential effects on different lipid classes. In the presence of lipid-rich medium, certain lipids accumulated after metformin treatment, which is consistent with a recent study showing that the certain classes of lipids accumulated in breast cancer cells after treatment with a fatty acid synthase inhibitor (20). Further, as a proof of concept we measured with stable isotopes, the incorporation of glucose into lipids.…”
Section: Discussionsupporting
confidence: 90%
“…As a control, MDA-MB-231 cells were treated with Takinib but not TNFα. Caspase 3/7 activity was determined as previously described (Alwarawrah et al, 2016). TNFα stimulation in the presence of Takinib induced caspase activity in MDA-MB-231cells in a dose-dependent manner, whereas unstimulated cells did not upregulate caspase activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The assay was performed as previously described (Alwarawrah et al, 2016; Howe et al, 2014). Cells were seeded at a density of 5,000 cells/well.…”
Section: Star Methodsmentioning
confidence: 99%
“…In addition, an antimicrobial agent triclosan42 and GSK219406943 have been shown to have a potent inhibitory activity in FASN. Recently, Alwarawrah et al44 showed that Fasnall, a novel thiophenopyrimidine-based FASN inhibitor, exerts potent antitumor activity against various breast cancer cell lines and is well tolerated in mice. Moreover, Fasnall reduces tumor volume and increases survival in a mouse breast cancer model.…”
Section: Anticancer Agents Targeting Lipid Metabolic Reprogrammingmentioning
confidence: 99%